Preliminary construction of an indicated model of perceptions of industrial prospects - an empirical study of tourism and hospitality education in Taiwan / Lee Wen-Chih - Lee, Wen-Chih (Universiti Teknologi MARA Cawangan Selangor, 2012)
This paper adopts "Convenience Sampling" for the questionnaire survey, and the objects of this research focus on in-school students in Southern Taiwan institutes to construct the indicated preliminary model. 250 questionnaires were sent directly to 10 academics at 6 schools by post, and 231 were retrieved. There were 12 components extracted, but parts of the components were absorbed into the same ones owing to the insufficiency of extracted essentials of the components after testing. Then, five components as a whole were summarized as "Personality Perceptions (PPs)", "Perceptions of Industry Development and the Government's Policy (PIDGP)", "Perceptions of the Employment Market and Employment Willingness (PEMEW)", "Curricular Designs (CDs)" and "Personality (PSNLT)", through the meaning of the essentials in each component. In accordance with the acquired statistical figures and verification of the research hypothesis, indications that the most influential and important levels of perceptions of industry prospects for the interviewees are "Perceptions of the Employment Market and the Employed Willingness (PEMEW)", and "Perceptions of Industry Development and the Government's Policy (PIDGP)"; however, the level of "Curricular Designs (CDs)" has the lowest influence and significance. This research sums up the main research findings after analyzing the conclusions and research hypotheses. 1) Most of the interviewees who have greater willingness to be employed in tourism and hospitality-related industries will obtain the updated information diligently and understand the tendencies in industry developments, and also improve or enhance their professional abilities to achieve their goals of working in this industry. 2) Most of the interviewees' personal perceptions of and personalities for the industry's prospects are quite weak and unstable. Furthermore, they are also lacking in enough multiabilities and career plans to fit the demands of the industry's developments.